(untitled) (Jurnal Ilmiah Teknik Sipil, 2026)
The development of an Electric Bus Rapid Transit (e-BRT) system in Sarbagita area requires the support of an integrated feeder transport system to ensure first-mile–last-mile connectivity and enhance public transport accessibility. This study aims to design feeder routes and service lines supporting the e-BRT system, analyze applicable operational systems, and evaluate financial feasibility based on Vehicle Operating Costs (VOC). A descriptive–quantitative approach was adopted, utilizing field survey data, secondary data, and public transport planning standards. The results indicate that the proposed feeder system consists of four integrated routes serving the Central Parking Kuta Station, namely FD-01 (East) with a route length of approximately 16 km, FD-02 (West) 7.3 km, FD-03 (South) 10.8 km, and FD-04 (North) 13 km (round trip). Operational analysis shows that cycle times range from 81.20 to 130.99 minutes, with fleet requirements of 9–14 vehicles and an average headway of approximately 9 minutes across all routes. From a financial perspective, total annual VOC ranges between Rp 141,335,385 and Rp 178,537,394, with the lowest operating cost per kilometer recorded on FD-01 at Rp 3,831.18/km and the highest on FD-D-02 at Rp 10,637.92/km. The VOC-based fare analysis indicates that the required operational fare ranges from Rp 11,551 to Rp 14,075 per passenger. Overall, the findings demonstrate that the proposed feeder transport system integrated with the e-BRT network is technically feasible, operationally effective, and financially viable, and has the potential to improve public transport accessibility and support the development of sustainable urban transportation.